RESPONSE OF TEN ORIGIN OF TARO TO PUDDLE LEVELS - Ridoi Manalu; Yulian Yulian; Widodo Widodo (BPFP Universitas Bengkulu, 2025)
[EFFECTS OF WATERLOGGING ON THE GROWTH OF TARO (Colocasia esculenta (L.) Schott) ACCESSIONS IN COASTAL AREA OF BENGKULU]. Taro (Colocasia esculenta (L.) Schott) is a vital tropical root crop with considerable potential for food diversification due to its nutritional and carbohydrate content. In Bengkulu Province, Indonesia—a region with rich taro genetic diversity in coastal agroecosystems—systematic evaluation of local accessions under waterlogging stress remains limited. This study assessed the effects of waterlogging depth and accession variability on taro growth using a Randomized Complete Block Design with three replications, evaluating ten local accessions under three waterlogging levels: 0 cm (control), 15 cm, and 30 cm. Results revealed significant (p < 0.01) differences among accessions for plant height, leaf width, leaf length, and stem diameter, indicating substantial genetic variation. Waterlogging significantly affected leaf width and length (p < 0.01) and plant height (p < 0.05), but not leaf number or stem diameter. No significant accession × waterlogging interaction was observed, suggesting consistent accession performance across treatments. Karang Tinggi (AK10) showed the greatest plant height (134.69 cm) and stem diameter (6.39 cm), while Bentiring 2 (AK4) exhibited the largest leaves. Moderate waterlogging (15 cm) did not impair growth relative to the control, but 30 cm waterlogging reduced leaf dimensions. These findings support the selection of resilient accessions like Karang Tinggi and Bentiring 2 for cultivation in flood-prone coastal areas and provide a foundation for breeding waterlogging-tolerant taro varieties. Full text pdf